A frame-shift mutation of PMS2 is a widespread cause of Lynch syndrome. Issue 6 (4th January 2008) - Clendenning, M; Senter, L; Hampel, H; Robinson, K Lagerstedt; Sun, S; Buchanan, D; Walsh, M D; Nilbert, M; Green, J; Potter, J; Lindblom, A; de la Chapelle, A
Abstract : Background: When compared to the other mismatch repair genes involved in Lynch syndrome, the identification of mutations within PMS2 has been limited (<2% of all identified mutations), yet the immunohistochemical analysis of tumour samples indicates that approximately 5% of Lynch syndrome cases are caused by PMS2. This disparity is primarily due to complications in the study of this gene caused by interference from pseudogene sequences. Methods: Using a recently developed method for detecting PMS2 specific mutations, we have screened 99 patients who are likely candidates for PMS2 mutations based on immunohistochemical analysis. Results: We have identified a frequently occurring frame-shift mutation (c.736_741del6ins11) in 12 ostensibly unrelated Lynch syndrome patients (20% of patients we have identified with a deleterious mutation in PMS2, n = 61). These individuals all display the rare allele (population frequency <0.05) at a single nucleotide polymorphism (SNP) in exon 11, and have been shown to possess a short common haplotype, allowing us to calculate that the mutation arose around 1625 years ago (65 generations; 95% confidence interval 22 to 120). Conclusion: Ancestral analysis indicates that this mutation is enriched in individuals with British and Swedish ancestry. We estimate that there are >10 000 carriers of this mutation in the USA alone. The identification of both the mutation and the common haplotype in one Swedish control sample (n = 225), along with evidence that Lynch syndrome associated cancers are rarer than expected in the probands' families, would suggest that this is a prevalent mutation with reduced penetrance.